THE IMPROVEMENT OF ENGLISH LANGUAGE ABILITY FOR INDUSTRIAL ENGINEERING STUDENTS THROUGH NON-ENGLISH LANGUAGE COURSES AT UNIVERSITY OF POTENSI UTAMA - Jane Elnovreny; Jernih Donda Sinurat (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
English language ability is very important in globalization era. Especially if someone want to work in multinational companies, English language ability is the most important requirement. Among students at University of Potensi Utama, there is a lack of awareness indication English learning, especially the Industrial Engineering study program. The aims of this research is to identify students' motivation and their abilities in English by learning process. Another purpose is to develop their English ability. The subjects of this research were second semester Industrial Engineering students. This research was carried out from February 2020 to August 2020. Type of this research is descriptive qualitative. Technique of data collection by using a questionnaire and document review of teaching materials, questions and exams to reveal how the improvement of non-language students' English ability and their motivation in the use of English. The data analysis model that used by researcher is the triangulation technique model. The research result shows an increase in students' motivation and English ability. The value of the increase in high students’ motivation from 30.19% to 64.05%, the increase in high students’ ability from 15.03% to 39.21%, this is also evident from the change of the pretest average score of 50.49 to the average value of posttest 71.09.